The Austrian School of Economics in the History of Economic Thought - Nori, Rodrigo Braian (2019)
This paper aims to present some contributions to the economic theory made by the main economists from the Austrian School, since their precursors - the scholastics of Salamanca - until F. A. Hayek’s contributions. Thereby we searchedtheoretical frameworks in literature such as books, papers and other media that propagate the Austrian School’s principles. This work was designed to study those precursors at first, then the contributions of Carl Menger through marginalism and methodological subjectivism, Bohm-Bawerk with his capital theory in the productive chain and his considerations about temporal preferences, Ludwig Von Mises with his arguments on economic calculation impossibility in a socialist society and finally the teachings of F. A. Hayek and his Austrian theory about economic business cycles.